The Strong State And Pancasila: Reflecting Human Rights in the Indonesian Democracy - Mutaqin, Zezen Zaenal (The Constitutional Court of the Republic of Indonesia, 2016)
The rights of every Indonesian citizens are protected by the 1945 Constitution. Does the reality matches with the normative regulations? Does democratization improves the protection of human rights especially in term of the religious freedom? We find that there is a discrepancy between the ideal written constitution and the reality. In this following essay I argue that the failure of Indonesian democratic regimes to protect human rights is the result of the lack of